OVERVIEW OF MESIODENS –A REVIEW - MONISHA.P.KHATRI,C.R.RI,; DR. A.VICTOR SAMUEL, M.D.S, (International Journal of Pharma and Bio Sciences, 2014)
Mesiodens is the most common supernumerary tooth in the maxillary anterior region which occurs less frequently in the primary dentition. Many theories have been put forward to explain the occurrence of mesiodens but the most acceptable from all of them is the hyperactivity theory with genetic theory gaining popularity. There is a vast classification for mesiodens that is explained with the help of a flowchart and diagrams in this paper. The main classification is according to morphology. Diagnosis of mesiodens is best done by clinical and radiographic examination. Management of mesiodens can be done either by extraction or by retention and observation of mesiodens. Early extraction is the best treatment option as it may prevent further complications. This paper reviews about mesiodens with comprehensive classification, clinical diagnosis and its management.